Magical mathematics : the mathematical ideas that animate great magic tricks - Diaconis, Persi (Princeton University Press, 2011)
Magical Mathematics reveals the secrets of amazing, fun-to-perform card tricks--and the profound mathematical ideas behind them--that will astound even the most accomplished magician. Persi Diaconis and Ron Graham provide easy, step-by-step instructions for each trick, explaining how to set up the effect and offering tips on what to say and do while performing it.